Are Antineoplastic Drug Acute Hypersensitive Reactions a Submerged or an Emergent Problem? Experience of the Medical Day Hospital of the Fondazione IRCCS Istituto Nazionale Tumori. Issue 1 (January 2014) - Ferrari, Laura AM; Fanetti, Giuseppe; Rossi, Fabio G; Brambilla, Maria C; Re, Barbara; Buzzoni, Roberto
Background: Acute hypersensitivity reactions are adverse events potentially associated with antineoplastic drug infusions. Their occurrence can be particularly relevant in an outpatient environment where time of administration and subsequent observation is limited to a short period of time. In addition, concern about the onset of more severe hypersensitivity reactions can limit subsequent use of crucial drugs. Methods: During a 3-year observational period, we collected a total of 240 infusional acute hypersensitivity reactions out of 56, 120 administrations performed, with an overall incidence of 0.4%. Results: In order of frequency, platinum derivatives, taxanes and monoclonal antibodies accounted for the highest incidences. Their relative frequency was: oxaliplatin, 2.5%; carboplatin, 0.4%; paclitaxel, 1.2%; docetaxel, 1.2%; trastuzumab, 1.2%, and rituximab, 1.2%. Conclusions: Since the number of chemotherapeutic agents is steadily increasing, much attention should be paid to such reactions, particularly when several administrations are performed daily, and where management of the potential risk associated with specific drugs is mandatory. Their occurrence represents an unpredictable, unexpected and often hard to manage contingency, and our opinion is that observation and consciousness of this issue are fundamental for its appropriate management. We describe our experience, emphasizing the role of this toxicity and explaining how this awareness allowed us to define some empirical rules to handle acute hypersensitivity reactions.